PERANCANGAN SISTEM INVENTORI BARANG BERBASIS WEB PADA RAPHAEL’S DIVAN - Adi Prayitno; M. Irham (Jurnal Publikasi Teknik Informatika, 2023)
Raphael's Divan is a company engaged in the furniture sector. In addition to selling furniture, Raphael's Divan also produces furniture, namely divans. Currently, data collection and report generationat Raphael's Divan is still done manually, so data information still has many shortcomings such asinappropriate stock of goods, lack of time efficiency, and data redundancy. Looking at the problems inRaphael's Divan, an inventory system application was made using the Prototype development method. Thisweb-based inventory system application in its design uses HTML, PHP, Java Script and for the database ituses MySQL. The creation of a web-based inventory information system application aims to increase theeffectiveness in data collection, reporting and information availability of goods, specifically raw materialsin Raphael's Divan.